Size‐Tunable Ni–Cu Core–Shell Nanoparticles—Structure, Composition, and Catalytic Activity for the Reverse Water–Gas Shift Reaction. Issue 6 (19th January 2022) - Heilmann, Maria; Prinz, Carsten; Bienert, Ralf; Wendt, Robert; Kunkel, Benny; Radnik, Jörg; Hoell, Armin; Wohlrab, Sebastian; Guilherme Buzanich, Ana; Emmerling, Franziska
Abstract : A facile and efficient methodology is described for the solvothermal synthesis of size‐tunable, stable, and uniform NiCu core–shell nanoparticles (NPs) for application in catalysis. The diameter of the NPs is tuned in a range from 6 nm to 30 nm and to adjust the Ni:Cu ratio from 30:1 to 1:1. Furthermore, the influence of different reaction parameters on the final NPs is studied. The NPs are structurally characterized by a method combination of transmission electron microscopy, anomalous small‐angle X‐ray scattering, X‐ray absorption fine structure, and X‐ray photoelectron spectroscopy. Using these analytical methods, it is possible to elucidate a core–shell–shell structure of all particles and their chemical composition. In all cases, a depletion from the core to the shell is observed, with the core consisting of NiCu alloy, surrounded by an inner Ni‐rich shell and an outer NiO shell. The SiO2 ‐supported NiCu core–shell NPs show pronounced selectivity of >99% for CO in the catalytic reduction of CO2 to CO using hydrogen as reactant (reverse water–gas shift reaction) independent of size and Ni:Cu ratio. Abstract : Size tunable bimetallic Ni–Cu nanoparticles are prepared by an adapted synthesis in a size range of 6 to 30 nanometers. The inner structure, consisting of a Cu–Ni alloy core, surrounded by a Ni‐rich shell, and a NiO shell, is revealed. These core‐shell‐shell nanoparticles show a pronounced selectivity for CO in the catalytic reduction of CO2 to CO.